CELL HEALTH LEARNING BASED ON DZIKRULLOH SPIRITUAL PRACTICE â€œHE NING CIPTO METAPHYSICS MEDITATIONâ€, TO BUILD A STRONG BODY IMMUNITY SYSTEM - Qosyim, Ahmad; Erman, Erman; Rosdiana, Laily; Susiyawati, Enny (Perkumpulan Pendidik IPA Indonesia (PPII), 2021)
This study aimed to describe the implementation of the Spiritual Practice-Based Learning Approach to Metaphysics Meditation